Behavior of immunocastrated pigs - Silva dos Santos, Rita de Kassia (2016)
The objective of this study was to evaluate the behavior of immunocastrated male pigs compared with females and castrated males during the period before and after full immunization. A total of 30 animals were divided into three treatments, with ten animals in each (females, barrows, and immunocastrated males). The experiment was divided into three periods: 70 to 80 days of age (period 1), 81 to 110 days of age (period 2), and 111 to 140 days of age (period 3). The behavior of animals during these stages was evaluated. Immunocastrated males showed a higher rate of aggressive and sexual behavior during period 2, which decreased after the second vaccine dose. Both barrows and immunocastrated males presented high locomotion in period 1, reducing the frequency of this activity in period 3. All analyzed animals had a higher level of activities such as drinking, playing, and sexual behavior in period 1 than in the other periods, decreasing during the experiment. The remaining behavioral responses did not differ between the studied categories. Immunocastrated males had higher proportions of undesirable behaviors (aggressive and sexual) related to the surgically castrated males and females, and these were reduced after the second vaccine dose. Immunocastration is effective in the reduction of behaviors such as agonistic and sexual at the same levels observed in females and surgically castrated males. However, immunocastrated pigs are more subject to these undesirable behaviors before full immunization.